Prevalence, Correlates, and Prognosis of Peripheral Artery Disease in Rural Ecuador—Rationale, Protocol, and Phase I Results of a Population-Based Survey: An Atahualpa Project-Ancillary Study - Oscar H. Del Brutto; Mark J. Sedler; Robertino M. Mera; Pablo R. Castillo; Elizabeth H. Cusick; Jadry A. Gruen; Kelsie J. Phelan; Victor J. Del Brutto; Mauricio Zambrano; David L. Brown (International Journal of Vascular Medicine)
Background. Little is known on the prevalence of peripheral artery disease (PAD) in developing countries. Study design. Population-based study in Atahualpa. In Phase I, the Edinburgh claudication questionnaire (ECQ) was used for detection of suspected symptomatic PAD; persons with a negative ECQ but a pulse pressure ≥65 mmHg were suspected of asymptomatic PAD. In Phase II, the ankle-brachial index will be used to test reliability of screening instruments and to determine PAD prevalence. In Phase III, participants will be followed up to estimate the relevance of PAD as a predictor of vascular outcomes. Results. During Phase I, 665 Atahualpa residents aged ≥40 years were enrolled (mean age: 59.5 ± 12.6 years, 58% women). A poor cardiovascular health status was noticed in 464 (70%) persons of which 27 (4%) had a stroke and 14 (2%) had ischemic heart disease. Forty-four subjects (7%) had suspected symptomatic PAD and 170 (26%) had suspected asymptomatic PAD. Individuals with suspected PAD were older, more often women, and had a worse cardiovascular profile than those with nonsuspected PAD. Conclusions. Prevalence of suspected PAD in this underserved population is high. Subsequent phases of this study will determine whether prompt detection of PAD is useful to reduce the incidence of catastrophic vascular diseases in the region.